Treatment of transpalatal nasality in a complex case with phonological disorder - Pascual-Soriano, Alberto; Cervera Mérida, José Francisco (Revista de Investigación en Logopedia, 2022)
The purpose of this case study was to describe the process of assessment and speech therapy intervention over a 9-year-old girl with hypernasality and phonological difficulties of perceptual and expressive nature. The phonetic and phonological level of the language, the nasal timbre through nasometry, the functional integrity of the velopalatopharyngeal structures and the hearing were assessed. The patient had a very distorted pronounciation of the sounds [d], [l] and [t] with characteristics of [n], while not being able to to distinguish them from the nasal consonant. The configuration of her oral cavity and her idiosyncratic articulatory base favored the phenomenon of transpalatal nasality: excessive presence of nasal resonance during the emission of none-nasal sounds in the absence of velopharyngeal dysfunction. An intensive treatment with the Nasometer II visual biofeedback tool was applied for the hypernasality interventional approach, as recommended by the existing literature for other known cases of nasality of functional origin. The treatment showed efficacy for voluntary control over the reduction of hyperrinolalia, but did not show effectiveness because the patient was not able to reduce nasal timbre in her spontaneous speech.
Keywords: Nasality; transpalatal nasality; phonological disorders; Nasometer